B-Raf and CRHR1 internalization mediate biphasic ERK1/2 activation by CRH in hippocampal HT22 Cells. - Bonfiglio, Juan José (2013)
CRH is a key regulator of neuroendocrine, autonomic, and behavioral response to stress. CRH-stimulated CRH receptor 1 (CRHR1) activates ERK1/2 depending on intracellular context. In a previous work, we demonstrated that CRH activates ERK1/2 in limbic areas of the mouse brain (hippocampus and basolateral amygdala). ERK1/2 is an essential mediator of hippocampal physiological processes including emotional behavior, synaptic plasticity, learning, and memory. To elucidate the molecular mechanisms by which CRH activates ERK1/2 in hippocampal neurons, we used the mouse hippocampal cell line HT22. We document for the first time that ERK1/2 activation in response to CRH is biphasic, involving a first cAMP- and B-Raf-dependent early phase and a second phase that critically depends on CRHR1 internalization and ß-arrestin2. By means of mass-spectrometry-based screening, we identified B-Raf-associated proteins that coimmunoprecipitate with endogenous B-Raf after CRHR1 activation. Using molecular and pharmacological tools, the functional impact of selected B-Raf partners in CRH-dependent ERK1/2 activation was dissected. These results indicate that 14-3-3 proteins, protein kinase A, and Rap1, are essential for early CRH-induced ERK1/2 activation, whereas dynamin and vimentin are required for the CRHR1 internalization-dependent phase. Both phases of ERK1/2 activation depend on calcium influx and are affected by calcium/calmodulin-dependent protein kinase II inactivation. Thus, this report describes the dynamics and biphasic nature of ERK1/2 activation downstream neuronal CRHR1 and identifies several new critical components of the CRHR1 signaling machinery that selectively controls the early and late phases of ERK1/2 activation, thus providing new potential therapeutic targets for stress-related disorders.